Power lines and birds: An overlooked threat in South America - Rebolo, Natalia (2023)
Power lines endanger birds around the world, as a large number of them are killed every year through electrocutions and collisions. This problem can have severe consequences at population level, particularly for threatened species. While this threat has been widely studied in different parts of the world, information from South America is scarce. Here, we review information from scientific and grey literature on the collision and electrocution of birds on power lines from this sub-continent. We complement this information with novel data provided by a citizen science project, electrical companies and field monitoring records. Our results show that although in South America scientific and anecdotal information on this topic is scarce, data suggests that this threat is present in many areas of this sub-continent and affects several species, some of which are seriously threatened. However, information on the most affected species, the number of individuals impacted, the most dangerous geographical areas and the effectiveness of mitigation action is scarce and mainly anecdotal. This is worrying, because South America is a hot spot of biodiversity with many threatened and endemic bird species. We urge conservationists to evaluate this problem in more detail, define areas where it is important to avoid power line installation and establish priority areas for implementation of effective mitigation actions. Scientific evidence shows that dangerous power lines require retrofitting, but this knowledge should also be applied to the new energy facilities and the establishment of national regulations, which would undoubtedly reduce the impact of this infrastructure on wildlife.